2022
DOI: 10.1186/s13018-022-03436-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for deep surgical site infection following surgically treated peri-ankle fractures: a case–control study based on propensity score matching

Abstract: Aims This study aims to identify the risk factors for deep surgical site infection (DSSI) following surgically treated peri-ankle fractures. Methods We performed a retrospective case–control study using the propensity score matching (PSM) method in 1:2 ratio, based on the 6 baseline variables, including age, gender, living area, insurance type, fracture location and surgical date. Data on patients who underwent surgical treatment of peri-ankle frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Some scholars believe that advanced age is a risk factor for wound complications, 22 diabetes is a recognised risk factor for infection 23 . Previous studies have also shown that injury mechanism, open fracture and wound classification are also risk factors for wound complications after ankle fracture 21,24,25 . In this study, we identified nine independent risk factors associated with an increased risk of postoperative wound complications in patients with ankle fracture.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Some scholars believe that advanced age is a risk factor for wound complications, 22 diabetes is a recognised risk factor for infection 23 . Previous studies have also shown that injury mechanism, open fracture and wound classification are also risk factors for wound complications after ankle fracture 21,24,25 . In this study, we identified nine independent risk factors associated with an increased risk of postoperative wound complications in patients with ankle fracture.…”
Section: Discussionmentioning
confidence: 78%
“… 23 Previous studies have also shown that injury mechanism, open fracture and wound classification are also risk factors for wound complications after ankle fracture. 21 , 24 , 25 In this study, we identified nine independent risk factors associated with an increased risk of postoperative wound complications in patients with ankle fracture. Including age ≥60 years old OR3.671 (1.875–5.937), complicated with diabetes OR 2.763 (1.236–4.852), BMI OR1.198 (1.143–1.324), current smoking OR2.727 (1.251–5.602), alcoholism OR1.143 (1.034–1.267), injury mechanism (high vs. low and medium energy) OR2.437 (1.238–4.786), open fracture OR1.943 (1.826–2.139), wound classification (II vs.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the incidence of surgical wound healing failure after malleolar fracture surgery was 19%, which is higher than the range of 3.3-6.8% previously reported. However, there were no cases of deep SSI, which have been reported to occur in 1.44-16% of cases in past studies [11][12][13][14].…”
Section: Discussionmentioning
confidence: 98%
“…Smoking, age and alcohol consumption were also identified as significant risk factors. Smoking impairs tissue oxygenation and healing, while aging is often associated with diminished physiological reserves and comorbidities, both of which can compromise postoperative recovery 27 . Alcohol consumption can impair immune function and wound healing, further increasing SSI risk.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking impairs tissue oxygenation and healing, while aging is often associated with diminished physiological reserves and comorbidities, both of which can compromise postoperative recovery. 27 Alcohol consumption can impair immune function and wound healing, further increasing SSI risk. An elevated ASA score indicates more severe systemic disease, which can compromise a patient's ability to recover from surgery and resist infection.…”
Section: Discussionmentioning
confidence: 99%